2018
DOI: 10.1186/s13018-018-0878-y
|View full text |Cite
|
Sign up to set email alerts
|

Laser-guided transtibial technique improved single-bundle reconstruction of anterior cruciate ligament

Abstract: BackgroundThe transtibial tunnel technique achieves equal length reconstruction of the anterior cruciate ligament (ACL). This study aimed to investigate whether transtibial tunnel technique can achieve anatomical reconstruction of ACL.MethodsFor 25 corpses, the anterior soft tissue of the knee joint was detached so that the ligamentous surface was fully exposed, then the knee joint was fixed at 90° with an external fixator and the anterior cruciate ligament was removed. Double-sided laser technology was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Surgeons mainly locate this by using bone markers visualized under arthroscopy, but it is difficult to achieve a perfect ACL anatomical reconstruction, and the operation may not always be successful (22). Many researchers have explored novel methods to accurately locate the ACL insertion point, and found that using a fluoroscopy navigation system, a laser location system, or a reconstruction navigation system based on 2D-3D registration could achieve an accurate bone tunnel position (23)(24)(25). Ni and colleagues (26) used CT data to determine the ACL insertion location in 20 cases of cadaveric knee joints.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons mainly locate this by using bone markers visualized under arthroscopy, but it is difficult to achieve a perfect ACL anatomical reconstruction, and the operation may not always be successful (22). Many researchers have explored novel methods to accurately locate the ACL insertion point, and found that using a fluoroscopy navigation system, a laser location system, or a reconstruction navigation system based on 2D-3D registration could achieve an accurate bone tunnel position (23)(24)(25). Ni and colleagues (26) used CT data to determine the ACL insertion location in 20 cases of cadaveric knee joints.…”
Section: Discussionmentioning
confidence: 99%